PEMBELAJARAN MATEMATIKA REALISTIK (PMR) PADA MATERI LUAS DI KELAS IV MI - ELDA HERLINA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
This research was aimed at figuring out whether there was influence of learning mathematics using realistic approach upon students’ achievement on mathematics, especially upon width, and whether there was influence of students’ attitudes upon the learning of mathematics.The data of the research were analyzed by employing descriptive statistic analysis. The finding showed that students responded positively toward realistic mathematic learning and realistic mathematic learning was effective in activating students. It was concluded that students who followed realistic mathematic learning showed better learning achievement than those of conventional one upon the topic of width. Kata Kunci: Pembelajaran, Matematika, Realistik, Luas